Lammproduktionens ekonomiska påverkan av MTR - Dahlstrand, Mattias (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
The Swedish consumption of lamb a increasing, and today we yearly eat a kilo of lamb per person each year. As a consequence the Swedish degree of self production according to lamb is steadily decreasing, and is today about 39 %.Today Swedish Meats is now cooperating with the Swedish lamb breeders organisation to raise that percentage. At the same time the European Union presents a new agricultural reform, the MTR (Mid Term Review). The shape of this new reform is not yet fully known, but the general policy has been more or less outlined. The new reform is split into three propositions: the farm model, the regional model and the mixed model. Right now the mixed model seems to be the winner. The reason for the European Union to put forward this proposition is that the old reform was considered not to be economically durable enough in the long range. The European Union also has to reduce the direct support and the export subsidies to agriculture. The purpose of this work is to show the economic consequences of the new reform on the lamb industry, and also investigate if it is of any interest to the sucklecow breeders to shift onto lamb breeding when the subsidy for keeping sucklecow, witch is important to these producers, is taken away. With the mixed model most of the subsidies are disengaged from the production, among them the subsidies for keeping sucklecow and ewes. This work shows what effect this has on four different kinds of farm industries: two of them breeding lamb, one producing sucklecow, and one having no animals at all. The intensive breeders will be the ones to lose most if the subsidy on ewes is disengaged. For the production of de cows the conditions will be all new when the subsidy for sucklecow is totally disengaged from the production. The mixed model also means that all agricultural land will be equally evaluated (that is they will get the same acreage subsidy for both cultivated and pasture land. The lamb industry could, though, have a good potential as the demand for grazing animals will increase if a large part of the pasture land is to be kept open.